2020
DOI: 10.4103/jispcd.jispcd_363_19
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perception of the professional role and competence of Swedish dental hygienists: A questionnaire and interview study

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Challenges to the dependability part of trustworthiness are the selection of categories and the researchers pre‐understanding 20 . The authors' experience with this patient category and qualitative methodology ranged from moderate to extensive 15,33,34 . The positive with this is a deep understanding of the disease and its progression when interpreting the participants’ answers as well as different perspectives when analysing the transcribed interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges to the dependability part of trustworthiness are the selection of categories and the researchers pre‐understanding 20 . The authors' experience with this patient category and qualitative methodology ranged from moderate to extensive 15,33,34 . The positive with this is a deep understanding of the disease and its progression when interpreting the participants’ answers as well as different perspectives when analysing the transcribed interviews.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, dental hygienists are licensed and work independently with oral examinations in all age groups. 63 Two experienced dental hygienists performed all the oral examinations and they calibrated their examination techniques and data collection before the study started. The examinations were carried out using established methods in dentistry, this we consider an important strength of the study leading to reliable data that are possible to replicate.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review of qualitative and quantitative research, good teamwork has been identified as driving dentists towards providing advice on dental caries prevention for their patients [16]. While dentists provide restorative caries therapy, preventive care is typically provided by licenced dental hygienists or is a task delegated to dental nurses [17]. This involvement of several clinical stakeholders in patientcentred care requires a solid understanding and practicing of team-based dentistry to coordinate tasks [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…While dentists provide restorative caries therapy, preventive care is typically provided by licenced dental hygienists or is a task delegated to dental nurses [17]. This involvement of several clinical stakeholders in patientcentred care requires a solid understanding and practicing of team-based dentistry to coordinate tasks [17,18]. Further, experiences from implementation of guidelines for services delivered in teamwork indicate a need for high clarity about the roles and responsibilities of each team member and sufficient capacity such as overflow chairs to avoid a need for an additional appointment [19].…”
Section: Introductionmentioning
confidence: 99%